The Role Of Strategic Leadership In Business Strategy Implementation: A Systematic Literature Review - Henry Martin Adriansyah; Sri Indrastuti (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
Strategic leadership has become a critical factor in ensuring the successful implementation of business strategies in an increasingly dynamic, uncertain, and competitive environment. While many organizations are capable of formulating effective strategies, failures often occur during the implementation phase due to leadership-related challenges. This study aims to analyze the role, relevance, and impact of strategic leadership on business strategy implementation. This study employed a Systematic Literature Review (SLR) approach following PRISMA guidelines. Relevant articles published between 2023 and 2025 were collected from ScienceDirect and other reputable academic sources. A total of 100 articles were identified and screened based on predefined inclusion criteria. The selected studies were analyzed to address three research questions concerning the relevance, role, and impact of strategic leadership in strategy implementation. The findings indicate that strategic leadership remains highly relevant in the contemporary business environment, as evidenced by the increasing number of related publications. Strategic leadership contributes significantly to strategy implementation through vision development, effective communication, decision-making, adaptability, and change management. Furthermore, strategic leadership enhances organizational agility and supports successful adaptation to technological disruption, digital transformation, and environmental uncertainty. Strategic leadership has a substantial impact on organizational performance and the effectiveness of business strategy implementation. Leaders who demonstrate adaptive, innovative, and visionary capabilities are better positioned to overcome implementation challenges and achieve sustainable competitive advantage in the VUCA era. Future organizations will increasingly require strategic leaders capable of integrating internal capabilities with external environmental demands